PENGARUH PERSEPSI MAHASISWA AKUNTANSI MENGENAI LINGKUNGAN KERJA AKUNTAN PUBLIK DAN ETIKA PROFESI AKUNTAN PUBLIK TERHADAP PILIHAN KARIR SEBAGAI AKUNTAN PUBLIK (STUDI KASUS PADA MAHASISWA AKUNTANSI UNISMA, UMM, DAN UM) - Ainun Asri; Moh. Amin; M. Cholid Mawardi (Universitas Islam Malang, 2020)
ABSRACTThis research purpose to know the effect of accounting students' perceptions of public accountant work environment and professional ethics of public accountants on career choices as public accountants. The population of this researchare accounting students of Malang Islamic University, University of Muhammadiyah Malang, and University of Negeri Malang 2016 to 2017. The data collection used quistioners sheets from google form. The sample of this research are 95 students. The result showed that accounting students' perception of public accountant work environment and professional ethics of public accountants have positive effect for career choices as a public accountant.Keywords : Accounting students, Work environment, Ethic of profession, Career choices